Learning via Video in Higher Education: An Exploration of Instructor and Student Perceptions - Miner, Steven; Stefaniak, Jill (Journal of University Teaching and Learning Practice, 2018)
The purpose of this study was to compare instructors and students perceptions regarding the use of video during instruction.Background Research exploring student opinions regarding their perceived gains in learning may identify learning behaviors that could be exploited by those providing instruction to increase student learning. The intention is to provide instructional designers and college professors with valuable information regarding the use of video for presenting knowledge, explaining cognitive processes, or demonstrating psychomotor skills in a higher education setting. This study used a survey design to explore perceptional differences between professors and students regarding the use and/or effectiveness of video instruction. Results supported multimedia video as a viable teaching resource to communicate course content. This study provided the impetus for further research into actual (versus self-reported) student review of video material and any positive effects on student learning outcomes based on their perceptions of the use of multimedia video presentations.